Allogeneic Mesenchymal Stem Cell Transplantation in Severe and Refractory Systemic Lupus Erythematosus: 4 Years of Experience. Issue 12 (December 2013) - Wang, Dandan; Zhang, Huayong; Liang, Jun; Li, Xia; Feng, Xuebing; Wang, Hong; Hua, Bingzhu; Liu, Bujun; Lu, Liwei; Gilkeson, Gary S.; Silver, Richard M.; Chen, Wanjun; et al.
Mesenchymal stem cells (MSCs) are multipotential nonhematopoietic progenitors and are capable of differentiating into several tissues of mesenchymal origin. We have shown that bone marrow-derived MSCs from both SLE patients and lupus-prone MRL/lpr mice are defective structurally and functionally. Here we observe the long-term safety and efficacy of allogeneic MSC transplantation (MSCT) in treatment-resistant SLE patients. Eighty-seven patients with persistently active SLE who were refractory to standard treatment or had life-threatening visceral involvement were enrolled. Allogeneic bone marrow or umbilical cord-derived MSCs were harvested and infused intravenously (1 × 10 6 cells/kg of body weight). Primary outcomes were rates of survival, disease remission and relapse, as well as transplantation-related adverse events. Secondary outcomes included SLE disease activity index (SLEDAI) and serologic features. During the 4-year follow-up and with a mean follow-up period of 27 months, the overall rate of survival was 94% (82/87). Complete clinical remission rate was 28% at 1 year (23/83), 31% at 2 years (12/39), 42% at 3 years (5/12), and 50% at 4 years (3/6). Rates of relapse were 12% (10/83) at 1 year, 18% (7/39) at 2 years, 17% (2/12) at 3 years, and 17% (1/6) at 4 years. The overall rate of relapse was 23% (20/87). Disease activity declined as revealed by significant changes in the SLEDAI score, levels of serum autoantibodies, albumin, and complements. A total of five patients (6%) died after MSCT from non-treatment-related events in the 4-year follow-up, and no transplantation-related adverse event was observed. Allogeneic MSCT resulted in the induction of clinical remission and improvement in organ dysfunction in drug-resistant SLE patients.